Qiraat 'Ashr and The Determination of The Concepts of Nasakh and Mansukh - Ismail Abd Halim; Azhar Muhammad; M. Jismani Yusoff (Rabbanica: Journal of Revealed Knowledge)
The concept of nasakh and mansukh is accepted by most scholars as one of the concepts in the interpretation of the Quran. However, some scholars deny the practice of this concept in interpreting the Quran. Verse 106 of Surah al-Baqarah is among the arguments used by most scholars in setting this concept. However, this sentence contains qiraat differences that can influence interpretation. Therefore, this article aims to unravel and reveal the influence of Qiraat 'Ashr in setting the concept of nasakh and mansukh and evaluate whether Qiraat 'Ashr can support the majority of scholars. The study was conducted based on a qualitative study approach. The primary data are obtained from the books of tafsir, qiraat and tawjih besides journals and theses concerned. It is analyzed through the istinbat and tarjih methods. The study results found that the difference in Qiraat 'Ashr in verse 106 of surah al-Baqarah is very influential in setting the concept of abrogation and mansukh while supporting the majority of scholars. It also reveals another aspect of the concept of nasakh and mansukh, which is to forget the verses of the Qur'an that have been revealed. In addition, it also features an element of affirmation in refuting any disobedience to the concepts of nasakh and mansukh. This study concludes that the difference between qiraat and its role in interpreting the Quran is indeed an exciting field to study because it can resolve the turmoil of understanding the Quranic texts or at least increase confidence in believing the Quranic texts base.